2010
DOI: 10.3155/1047-3289.60.4.489
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Carbon Dioxide from Gas Streams via Mesoporous Spherical-Silica Particles

Abstract: A relatively new mesoporous silica sorbent for environmental protection applications (i.e., mesoporous spherical-silica particles [MSPs]), was modified by N- [3-(trimethoxysilyl)propyl]ethylenediamine (EDA) solution and was tested for its potential in the separation of carbon dioxide (CO 2 ) from flue gas. The CO 2 adsorption capacity of MSP and MSP(EDA) increased with temperature from 20 to 60°C but decreased with temperature from 60 to 100°C. The mechanism of CO 2 adsorption on both samples is mainly attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The moisture in the CO 2 gas cylinder was measured to be 5% relative humidity, which corresponds to an absolute moisture content of 0.16% (v/v) and is much lower compared to the CO 2 concentration. The effect of moisture content on the MSP can be referred to our prior study [13]. It indicated that at moisture content of less than 4% (v/v), the moisture content has no effect on the CO 2 adsorption capacity for the MSP adsorbent.…”
Section: Application As Adsorbents For the Capture Of Comentioning
confidence: 98%
“…The moisture in the CO 2 gas cylinder was measured to be 5% relative humidity, which corresponds to an absolute moisture content of 0.16% (v/v) and is much lower compared to the CO 2 concentration. The effect of moisture content on the MSP can be referred to our prior study [13]. It indicated that at moisture content of less than 4% (v/v), the moisture content has no effect on the CO 2 adsorption capacity for the MSP adsorbent.…”
Section: Application As Adsorbents For the Capture Of Comentioning
confidence: 98%
“…Hicks et al 38 fabricated a covalently tethered hyperbranched aminosilica adsorbent, which is capable of adsorbing CO 2 reversibly with a high capacity of 3.1 mmol g Ϫ1 at 298 K and multicycle stability. Recently, Lu et al 39 synthesized amine-modified mesoporous spherical silica particles, which are efficient for CO 2 capture, and their adsorption performance can be maintained during 16 cycles of adsorption and thermal regeneration.…”
Section: Technical Papermentioning
confidence: 99%
“…Lu et al [148] showed that mesoporous silica spherical particles (MSPs) can be synthesized using low-cost Na 2 SiO 3 thus they can be cost-effective adsorbents for CO 2 separation from flue gas [149, 150]. …”
Section: Co2 Separation Technologiesmentioning
confidence: 99%